Subungual Onycholemmal Cysts: A Case Report - Erika Lydrup; Anette Pedersen Pilt; Volker-Jürgen Schmidt; Hannah Trøstrup (Karger Publishers, 2021)
Subungual onycholemmal cysts (SOCs) are rare nail abnormalities. The clinical findings vary and include onychodystrophy, ridging, nail bed pigmentation, and thickening, but most often SOCs do not cause any symptoms and are accidental findings. In this case report, we present a case of a woman with pigmentation of the toenail, suspect for melanoma. Surprisingly, the histopathological examination showed SOCs. We discuss the histological features of SOCs, etiology, and differential diagnoses.